Tools and Approaches for Dissecting Protein Bacteriocin Import in Gram-Negative Bacteria - Atanaskovic, Iva; Kleanthous, Colin (Frontiers in Microbiology, 2019)
Bacteriocins of Gram-negative bacteria are multi-domain proteins that target and kill bacteria, usually of the same species. There is increasing interest in bacteriocin import, especially because of their potential as new antimicrobials to combat the rise in antibiotic resistant bacteria. To translocate across the cell envelope and cause cell death, bacteriocins hijack nutrient uptake pathways. Their import is energized by parasitizing intermembrane protein complexes coupled to the proton motive force (PMF), which delivers a toxic domain into the cell. A plethora of genetic, structural, biochemical and biophysical methods have been used to find cell envelope components involved in bacteriocin import since their discovery in the 1920s. Here, we review the various approaches that now exist for investigating bacteriocin import, and highlight areas of research that will need methodological innovations in order to fully understand the molecular mechanisms by which bacteriocins translocate into cells. We also highlight how bacteriocins can be used to probe the organization and architecture of the Gram-negative cell envelope itself.